Hubungan Antara Penggunaan Game Edukasi Duolingo Dengan Motivasi Dan Hasil Belajar Siswa Mata Pelajaran Bahasa Arab Di Madrasah Aliyah Perguruan Muallimat Cukir Diwek Jombang - Abdul Natsir; Muhammad Najihul Huda; Suci Evi Dianingsih (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2026)
ABSTRACT The integration of gamification-based technology in education has been increasingly adopted and is believed to enhance students’ motivation and academic performance. This study aims to examine the relationship between the use of Duolingo and students’ motivation and learning outcomes in Arabic subjects. A quantitative approach with a correlational method was employed. The population consisted of students from Madrasah Aliyah Perguruan Muallimat Cukir, selected through purposive sampling. Data were collected using a validated and reliable questionnaire, and analyzed using Partial Least Squares (PLS) with SmartPLS 4 software. The findings reveal that Duolingo significantly affects learning motivation (coefficient 0.858; p < 0.05) and learning outcomes (coefficient 0.759; p < 0.05). These results indicate that gamification-based applications can enhance student participation, engagement, and academic achievement in Arabic language learning. Keywords: Gamification, Learning Media, Academic Achievement